Pelatihan Manajemen Penyimpanan Online (Cloud Storage) pada Guru SMP Al-Hamidiyah Palembang - Diana Diana; Iin Seprina; Suzy Oktaria Kunang (Universitas Mathla'ul Anwar Banten, 2021)
CLOUD STORAGE MANAGEMENT TRAINING FOR TEACHERS OF SMP AL HAMIDIYAH PALEMBANG. Cloud storage has many facilities, including document upload and download facilities, document change history viewing facilities, document sharing and security facilities, document printing facilities and document translation facilities. Currently, there are many online storage applications that can be accessed for free, have large and permanent storage capacity. However, it is very unfortunate that this cloud storage technology has not been optimally utilized by the Al Hamidiyah Junior High School teacher in Palembang. Most of them only know the term, do not have knowledge about how to use this technology. To overcome this problem, online storage management training (cloud storage) has been conducted for teachers of SMP Al Hamidiyah Palembang. This training is carried out using the zoom meeting facility to avoid the spread of the COVID-19 virus which is currently endemic. In the presentation of the material, the PkM team demonstrated how to operate the google drive and drop box and the participants also practiced it directly on their respective laptops. Based on the results of the pretest and posttest, facts were obtained about increasing the knowledge of Al Hamidiyah Middle School teachers about cloud storage. In addition, at the end of the training, questionnaires were distributed resulting in 92.3% of SMP Alhamidiyah Palembang teachers stating that this training was very useful and 76.9% of them stated that the training material was very easy to understand.